2.4 GHz Rectifier Antenna for Radiofrequency-based Wireless Power Transfer: Recent Developments, Opportunities, and Challenges - Muhammad Miftahul Amri; Liya Yusrina Sabila (Jurnal Elektronika dan Telekomunikasi, 2023)
The use of radio frequency (RF) energy for wireless power transfer (WPT) has gained significant attention in recent years due to its potential for powering electronic devices without the need for wires or batteries. A key component of RF-based WPT systems is the rectenna, which converts RF energy into usable DC power. This article provides an overview of recent developments, opportunities, and challenges in the design of 2.4 GHz rectennas for RF-based WPT applications. We have searched major online libraries extensively for studies regarding the 2.4 GHz rectenna. As a result, 35 high-quality studies published between 2010 and 2023 were gathered. In the discussion section, we begin by presenting the basic principles of rectenna design and the key parameters that affect its performance, such as the antenna characteristics, rectifier capabilities, and nonlinearity properties of the rectifier. We then highlighted recent advancements in rectenna design, including novel approaches for improving efficiency and power transfer capability, such as the involvement of hybrid solar cell-rectenna structures, transistor-based rectifiers, and bridge rectifiers. Finally, the article concludes by identifying future opportunities, research directions, and open challenges in the design and optimization of rectennas for RF-based WPT, including the development of compact, low-cost, and high-performance rectennas for a wide range of applications. Overall, this article provides a comprehensive overview of the state-of-the-art of 2.4 GHz rectenna design for RF-based WPT and highlights the exciting opportunities and challenges for this rapidly growing field.